Efectos de la impulsividad y el consumo de alcohol sobre la toma de decisiones en los adolescentes - Caña, María Laura (2015)
Background: adolescence is a period associated with the onset and progression of alcohol consumption. At this stage are also frequent impulsive behaviors and risky decision-making (DM). Aim: To evaluate pattern of alcohol consumption (PAC) in male and female adolescents, their different levels of impulsivity and how these variables affect decision-making. Methodology: Using a latent class analysis several PAC of 230 adolescents aged 14 to 17 years were determined. Design: A prospective ex post facto crossover design with Positive Urgency (Low / High), PCA (Moderate / Binge) and Sex (Female / Male) as factors was used. DM was assessed in 78 participants who joined the study groups. Results: binge male consumers, compared with moderate, performed better, but their performance declined at the end of the test. Within the group of participants with low positive urgency, those with a binge PAC, made more advantageous DM. Conclusions: PAC and impulsivity trait appear to influence DM in adolescents.